Effect of long‐term (2 years) exposure of mouse brains to global system for mobile communication (GSM) radiofrequency fields on astrocytic immunoreactivity. Issue 3 (20th February 2015) - Court‐Kowalski, Stefan; Finnie, John W.; Manavis, Jim; Blumbergs, Peter C.; Helps, Stephen C.; Vink, Robert
Abstract : This study was designed to determine whether long‐term (2 years) brain exposure to mobile telephone radiofrequency (RF) fields produces any astrocytic activation as these glia react to a wide range of neural perturbations by astrogliosis. Using a purpose‐designed exposure system at 900 MHz, mice were given a single, far‐field whole body exposure at a specific absorption rate of 4 W/kg on five successive days per week for 104 weeks. Control mice were sham‐exposed or freely mobile in a cage to control any stress caused by immobilization in the exposure module. Brains were perfusion‐fixed with 4% paraformaldehyde and three coronal levels immunostained for glial fibrillary acidic protein (GFAP). These brain slices were then examined by light microscopy and the amount of this immunomarker quantified using a color deconvolution method. There was no change in astrocytic GFAP immunostaining in brains after long‐term exposure to mobile telephony microwaves compared to control (sham‐exposed or freely moving caged mice). It was concluded that long‐term (2 years) exposure of murine brains to mobile telephone RF fields did not produce any astrocytic reaction (astrogliosis) detectable by GFAP immunostaining. Bioelectromagnetics. 36:245–250, 2015. © 2015 Wiley Periodicals, Inc.